Die vegetationsgeographische Gliederung einer Stadt: Ein Versuch auf der Ebene statistisch-administrativer Raumeinheiten und am Beispiel der Stadt Osnabrück - Hard, Gerhard; Otto, Günter (ERDKUNDE, 1985)
At the outset three different levels of description of vegetation are shortly described. The sigma-sociological method is preferred to the floristic and the simple sociological method. In the following chapters the (eleven) plant communities, on which our investigation is based, are first described. Then the spatial structure of the town according to the distribution of these eleven plant communities is shown. Already on the basis of the 15 town-districts, but even better on the lower level of the 76 administrative units, a relatively differentiated structure is found (see Figs.1-4 and Tables 1 a. 2). This vegetational structure can easily be interpreted by the socio-economic and functional structure of the town. The fundamental findings can be generalized, at least for the region of north-western Germany. One aim of the paper was to find out if it is possible to carry out the examination of the vegetational structure of a town even on the basis of the urban administrative districts. The result was positive. This opens up the prospect of combining aspects of plant geography with the social ecology of a town.